Geo-environment and seismic process: problems of management - Shuman, V. N. (Geofizicheskiy Zhurnal, 2011)
On the basis of the concept on geomedium as an energy-saturated open nonlinear system with attraction of elements from the apparatus of modern theory of complicated nonlinear systems management, possibilities and methods of impact are considered of controlled (MHD-generator, electro-exploration generator device, underground nuclear explosion) and natural (magnetic storms) sources. As is well known, in ultimately energy-saturated media relatively small impact as to its capacity can have its result as strong path modification in phase space. A set of well known examples and attempts of such an impact has been considered. In this case, taking contemporary experience and possibilities of seismic processes monitoring into account, much more weakened purposes are set, in particular, creation of regimes with partially defined properties or restoration of a regime of a background movement of blocks. Explanation of physical mechanisms of such an impact is supported by a concept of dynamically unstable geomedium proposed by I. L. Gufeld based on ideas of reaction of blocky geomedium on interaction with a flow of light gases. It is noted that the noise in such systems can be a structural factor, which produces an increase of coherence degree or a degree of order in the system. It is underlined in this connection a possible role and importance of scholastic resonance in the management of distributed systems.Problems of coordination of management problem with results of monitoring aimed at either direct forecast of characteristics of the process for some temporal interval forward or selection of the intervals of «anomalous behavior», which can become in some cases the precursors of dramatic changes in the system for future are discussed.